Rapid non-invasive genotyping of reporter transgenic mammals. (May 2012) - Garrels, Wiebke; Cleve, Nicole; Niemann, Heiner; Kues, Wilfried A.
Here we describe a non-invasive method for rapid and highly reproducible genotyping of transgenic mammals with ubiquitous expression of fluorophore reporters. Hair samples from transgenic mice and pigs with systemic expression of the fluorophore reporter Venus were analyzed with a fluorescence microscope in few minutes. The hair samples can be preserved for long-term storage at ambient temperature conditions. This non-invasive method is useful for genotyping of transgenic large animals and contributes to animal welfare by reducing stress and discomfort of the animals during sample collection.